Pengaruh Terapi BagaPule untuk Mengurangi Nyeri Kepala Lansia dengan Hipertensi - Iskandar Iskandar; Dewi Sartika; Maqfiratul Afra; Vriska Elvianda (Faletehan Health Journal, 2024)
Headache is a problem complained by 20% of hypertensive patients. The pain can cause various effects ranging from mild discomfort to disrupting quality of life. BagaPule therapy is a combination of warm compress and massage on the gate of consciousness points, one of the non-pharmacological ways to reduce headaches. Hypertensive patients will feel a warm sensation in the neck to the head area after applying warm compresses. This study aimed to examine the influence of BagaPule therapy administration to reduce headaches in elderly patients with hypertension in Lhok Bengkuang, Aceh. The research design used in this study was quasi-experimental with equivalent control group design. The participants of this study were all elders suffering from hypertension, with the total of 36 participants selected by using simple random sampling technique. The statistical analysis was conducted by using Wilcoxon and Mann-Whitney test. The results of univariate analysis in the control group showed that the majority of elderly headache levels were categorized as moderate with 12 respondents (48%) and the intervention group showed that the majority of elderly headache levels were categorized as moderate with 14 respondents (51.9%). The bivariate analysis results showed that there was an influence of BagaPule therapy on reducing headaches in elderly patients with hypertension (p-value 0.032). BagaPule therapy was highly positive to reduce pain and can be recommended as an innovation in complementary health.